Remote Ischemic Preconditioning Reduces the Risk of Contrast-Induced Nephropathy in Patients with Moderate Renal Impairment Undergoing Percutaneous Coronary Angiography: A Meta-Analysis - Jin Deng; Yi Lu; Jihong Ou; Xiaofei Shao; Xin Wang; Hongping Xie (Karger Publishers, 2020)
Background/Aims: This meta-analysis evaluated the effects of remote ischemic preconditioning (RIPC) on the risk of contrast-induced nephropathy (CIN) in patients undergoing percutaneous coronary intervention/coronary angiography (PCI/CA). Methods: PubMed, Embase, and the Cochrane Central Register of Controlled Trials databases were searched for randomized controlled trials (RCTs) that assessed the effect of RIPC on CIN in patients undergoing PCI/CA. The main outcomes of interest were the incidence of CIN 48-72 h after CA, the levels of serum creatinine, cystatin C, neutrophil gelatinase-associated lipocalin, and estimated glomerular filtration rate (eGFR), mortality, and requirement of hemodialysis and rehospitalization. The analysis was conducted using the random-effect model due to the expected heterogeneity among different studies. Results: In total, 16 trials covering 2,048 patients were identified. By assessing the methodological quality of the included studies through the Cochrane risk of bias, we found that of the 16 RCTs, 3 had a low risk of bias, 6 a high, and 7 an unclear risk. The application of RIPC decreased the incidence of CIN (relative risk, RR, 0.50, 95% confidence interval, CI, 0.39-0.65; p < 0.001). Subgroup analyses showed that RIPC decreased the incidence of CIN in patients with eGFR <60 mL/min/1.73 m2 (RR 0.53, 95% CI 0.38-0.75; p < 0.001) but not in patients with eGRF ≥60 mL/min/1.73 m2 (RR 0.82, 95% CI 0.35-1.94; p = 0.66) at baseline. Furthermore, the increase in serum creatinine was significantly lower in patients with RIPC compared to control patients (standardized mean difference -1.41, 95% CI -2.46 to -0.35; p = 0.009). Conclusions: Based on 16 RCTs, this meta-analysis shows that RIPC can reduce the risk of CIN in patients with moderate renal impairment undergoing PCI/CA. However, this needs to be confirmed by further high-quality evidence.